2023
DOI: 10.3390/pharmaceutics15041228
|View full text |Cite
|
Sign up to set email alerts
|

Infant Exposure to Antituberculosis Drugs via Breast Milk and Assessment of Potential Adverse Effects in Breastfed Infants: Critical Review of Data

Abstract: Infants of mothers treated for tuberculosis might be exposed to drugs via breast milk. The existing information on the exposure of breastfed infants lacks a critical review of the published data. We aimed to evaluate the quality of the existing data on antituberculosis (anti-TB) drug concentrations in the plasma and milk as a methodologically sound basis for the potential risk of breastfeeding under therapy. We performed a systematic search in PubMed for bedaquiline, clofazimine, cycloserine/terizidone, levofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…No maternal blood was taken to calculate the milk-plasma concentration ratio; however, an earlier study of older-generation quinolone exposure in pregnant and lactating women indicated high concentrations in breastmilk (>75% relative to maternal plasma concentrations even two hours after dosing) [14]. The clinical implications of fluoroquinolone exposure in breastmilk have not been widely reported; however, based on available data, the risks to the breastfeeding infant are considered to be negligible given the extremely low estimated dose delivered to the infant through breastmilk in this case [8].…”
Section: Fluoroquinolones (Levofloxacin and Moxifloxacin)mentioning
confidence: 91%
See 4 more Smart Citations
“…No maternal blood was taken to calculate the milk-plasma concentration ratio; however, an earlier study of older-generation quinolone exposure in pregnant and lactating women indicated high concentrations in breastmilk (>75% relative to maternal plasma concentrations even two hours after dosing) [14]. The clinical implications of fluoroquinolone exposure in breastmilk have not been widely reported; however, based on available data, the risks to the breastfeeding infant are considered to be negligible given the extremely low estimated dose delivered to the infant through breastmilk in this case [8].…”
Section: Fluoroquinolones (Levofloxacin and Moxifloxacin)mentioning
confidence: 91%
“…Low linezolid levels in breastmilk are unlikely to be harmful to nursing infants but concerns for adverse effects cannot be ruled out [8]. No routine monitoring is currently recommended, but assessment of full blood count and differential in the infant might be clinically indicated.…”
Section: Who Categorization Of Anti-tuberculosis Medicationsmentioning
confidence: 99%
See 3 more Smart Citations